Microarray microRNA profiling of urinary exosomes in a 5XFAD mouse model of Alzheimer's disease. Issue 3 (9th June 2021) - Song, Zhiqi; Qu, Yajin; Xu, Yanfeng; Zhang, Ling; Zhou, Li; Han, Yunlin; Zhao, Wenjie; Yu, Pin; Zhang, Yu; Li, Xianglei; Qin, Chuan
Abstract: Background: Alzheimer's disease (AD) is an incurable and irreversible neurodegenerative disease, without a clear pathogenesis. Therefore, identification of candidates before amyloid‐β plaque (Aβ) deposition proceeds is of major significance for earlier intervention in AD. Methods: To explore the potential noninvasive earlier biomarkers of AD in a 5XFAD mouse model, microRNAs (miRNAs) from urinary exosomes in 1‐month‐old pre‐Aβ accumulation 5XFAD mice models and their littermate controls were profiled by microarray analysis. The differentially expressed miRNAs were further analyzed via droplet digital PCR (ddPCR). Results: Microarray analysis demonstrated that 48 differentially expressed miRNAs (18 upregulated and 30 downregulated), of which six miRNAs – miR‐196b‐5p, miR‐339‐3p, miR‐34a‐5p, miR‐376b‐3p, miR‐677‐5p, and miR‐721 – were predicted to display gene targets and important signaling pathways closely associated with AD pathogenesis and verified by ddPCR. Conclusions: Urinary exosomal miRNAs showing differences in expression prior to Aβ‐plaque deposition were identified. These exosomal miRNAs represent potential noninvasive biomarkers that may be used to prevent AD in clinical applications.